2023
DOI: 10.1017/s0003055422001484
|View full text |Cite
|
Sign up to set email alerts
|

Participation, Development, and Accountability: A Survey Experiment on Democratic Decision-Making in Kenya

Abstract: Many governments in semi-democratic regimes have adopted participatory democratic institutions to promote development and accountability. But limited resources, weak civil society, and a history of authoritarian politics make building subnational democratic institutions daunting. Do participatory institutions expand accountability in these environments? We address this question by evaluating citizen decision-making in Kenya’s local participatory processes. We first administered a survey experiment surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…While all counties reported some degree of public consultation about upcoming county budgets in previous years, these public consultations were under-resourced and fleeting. In no cases did previous public consultations rise to the level of a well-resourced and operated participatory budgeting program, such as those studied in other Kenyan counties (Touchton and Wampler 2023). This assessment included both government participatory structures and also a sparse mixture of previous efforts by NGOs to generate participatory processes in a handful of wards.…”
Section: Strengthening Devolution and The Ward Development Plan Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…While all counties reported some degree of public consultation about upcoming county budgets in previous years, these public consultations were under-resourced and fleeting. In no cases did previous public consultations rise to the level of a well-resourced and operated participatory budgeting program, such as those studied in other Kenyan counties (Touchton and Wampler 2023). This assessment included both government participatory structures and also a sparse mixture of previous efforts by NGOs to generate participatory processes in a handful of wards.…”
Section: Strengthening Devolution and The Ward Development Plan Modelmentioning
confidence: 99%
“…Despite its widespread adoption, initial enthusiasm for participatory planning has been tempered by a number of ambiguous or null empirical findings regarding its social impact. While systematic reviews of participatory planning have consistently found modest positive economic welfare effects and increased access to public goods, evidence on social impact-democratic governance, increased social capital, and equitable social norms-is markedly weaker and inconsistent (Casey 2018;Mansuri and Rao 2013;Touchton and Wampler 2023;White, Menon, and Waddington 2018;Wong 2012) 1 . These reviews have largely advanced the pessimistic conclusion that participatory planning does not 'work' as a class of interventions with regard to social change or, at minimum, its operation may require supportive factors often absent in implementation contexts (Touchton and Wampler 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, citizen participation in local decision making processes promotes accountability (Touchton & Wampler, 2023). This means that citizens are in a position to be informed by their local leaders about actions taken on their behalf.…”
Section: Introductionmentioning
confidence: 99%